The Effect of The Education Background of The Chief Financial Officer and Profitability on Audit Report Lag - Uzliawati , Lia; Muttaqin, Galih Fajar; Kurnia , Raisa Nur (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aims to determine the effect of the chief financial officer's educational background and profitability on audit report lag. The research object is infrastructure sector companies for the 2018-2021 period. The method in this research is quantitative research with multiple linear regression tests. The sampling technique used is the purposive sampling method. Based on the study's results, (1) CFO's educational background does not affect audit report lag. (2) Profitability has a positive effect on audit report lag. The limitations of this study are the possibility of other independent variables that can explain in more detail the audit report lag phenomenon.